Profile of Blended Learning Implementation in Learning Activities - Eka Yulia Syahrawati; Endang Susantini; Sifak Indana (IJORER : International Journal of Recent Educational Research, 2022)
Study aims to describe and analyze of blended learning implementation in learning activities. The method applied in this research is a literature review that is sourced from the results of previous studies that have been selected from Google Scholars. The steps applied in this study are identifying journals/articles about blended learning, analyzing the definition of blended learning, synthesizing opportunities and activities in implementation of blended learning, analyzing barriers to implementing blended learning, and making conclusions. From the results of the analysis of 30 selected works of literature, the implementation of blended learning can be done by teaching it as a learning model, teaching it by combining it with other learning strategies or models, teaching it with the help of an LMS, and teaching it with the help of social media. Furthermore, the application of blended learning is able to support activities that can train students' 21st century skills. The implementation of blended learning requires careful planning and requires an understanding of student characteristics and the availability of supporting facilities and infrastructure. This study can provide an overview of the opportunities to apply blended learning in learning activities.